The Response of Banking Sectors to the Covid-19 Pandemic in Indonesia Stock Exchange - Isnaini Nuzula Agustin; Agustino Agustino (Almana : Jurnal Manajemen dan Bisnis, 2022)
The COVID-19 pandemic that hit Indonesia in early March 2020 had an impact on the capital market, especially on the banking sector. This study aimed to find out the effect of the Daily Growth in Total Confirmed Cases and Daily Growth in Total Death Cases, Recovery Cases, and Social Restrictions on the stock return of the banking sector on the Indonesia Stock Exchange. This study will contribute in two ways. First, we engaged with a particular sector, namely the banking sector which is relatively scarce in the pertaining literature. Second, we involve the role of government intervention, on which, The Large-Scale Social Restrictions (PSBB) as one of the independent variables. The data were collected from companies engaged in the banking sector as many as 46 companies between March 1, 2020, and July 31, 2021. Through Panel Regression with EVIEWS software, the finding revealed that Daily Growth in Total Death Cases and Recovery Cases had a significant effect on stock return. While the Daily Growth in Total Confirmed Cases and PSBB appears to have an insignificant effect on Stock Market Return. This study contributes to investors and investment managers in making decisions in the stock market by paying attention to information related to the Covid-19 cases in Indonesia.